Advancing Educators Towards Social Justice Through Policy Analysis - Courtney J Hoffhines; Susan Yelich Biniecki (The Advocate, 2023)
Both pre-service and practicing educators are entering classrooms with limited preparation for the social landscape, affecting a range of professional considerations such as educational equity, culturally responsive teaching, and effective assessment. In an effort to consider greater impact and meaningful development of teachers for social justice concepts, this study is aimed directly at K-2 Kansas classrooms. A review of KSDE policies, utilizing a critical policy discourse analysis, allowed for the consideration of plausible responses for educational change regarding the advancement of educators for social justice. This research demonstrates the opportunity that exists within policy to create greater awareness for social justice issues within schools, as well as the opportunity to develop more effective educators through operationalizing language to improve educational impact.
Keywords: policy analysis; social justice education; critical pedagogy; K-12 education